LIFE-THREATENING INFECTION IN THIAMAZOLE INDUCED AGRANULOCYTOSIS: A CASE REPORT - Nurul, Enung Cahya; Soetedjo, Nanny NM; Sumardi, Uun; Ritonga, Ervita; Kusumawati, Maya; Wijaya, Indra; Wijaya, Alma; Permana, Hikmat (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Idiosyncratic antithyroid drug (ATD)-induced neutropenia and agranulocytosis are rare but potentially fatal. Severe sepsis was found in half of the patients, and the mortality rate was 6.7%. Cross-reactive ATD-induced agranulocytosis occurs in 15.2% of cases. A 23-year-old female with a history of Graves’ disease was admitted to the emergency room with abdominal pain and a sore throat. She was on thiamazole treatment for 3 months. There were signs of sepsis and diffuse abdominal pain. Leucocytes were 470/µL and the absolute neutrophil count was 19/µL. This case has been assessed and managed as appendicitis with severe sepsis. Appendicular perforation was discovered during laparotomy exploratory. Propylthiouracil (PTU) was introduced to replace thiamazole and granulocyte colonystimulating factors (GCSF) have been given to shorten the recovery time. Leucocyte counts returned to normal after 14 days of treatment. There was no agranulocytosis crossreaction by PTU. Early diagnosis is essential for proper treatment and a good prognosis.